Functional Structure of Industrial Objects - Rudenko, Viktor; Rudenko, Taras; Rudenko, Mariia (International Journal of Engineering and Technology, 2018)
Architecture as an order of human society should correspond to the functional, aesthetic, time needs and financial capabilities of all strata of society.  In this article described the main functional division of industrial objects system.When designing industrial objects, the main task of the architect is to create a construction that would be most suitable for the technological process of production. That is, he must take into account all the factors and conditions that govern the hierarchical structure of the industry and design a factory or plant that would be a modern element of the production system. Back in 1923 A. Rozenberg, in his book "Philosophy of Architecture", wrote: "It is impossible to properly design an architectural structure, not knowing precisely the organization of the process for which it is intended. And therefore, the deeper the architect will penetrate into its details of the organization, the more accurate it will clear itself to all the requirements imposed on the organization of the process, its course, the properties of the individual components of the mass of the process, and will establish the scheme of the process - that the conformity of the architectural structure to the process taking place in it will be more perfect, and the better will be the construction. "[1].